Geographic distribution and time trends of water-pipe use among Iranian youth and teenage students: A meta-analysis and systematic review. Issue 2 (2nd May 2023) - Afrashteh, Sima; Ansarifar, Akram; Vali, Mohebat; Nami Nazari, Leila; Keshtkar, Nasrin; Memar, Sara; Mohebbi, Elham; Hadji, Maryam; Ostovar, Afshin; Zendehdel, Kazem; Marzban, Maryam
Abstract: Water-pipe tobacco smoking is harmful to health, yet its rate of prevalence remains uncertain. Recent evidence has shown that the prevalence of water-pipe smoking among students is higher than in the general population. In this study, a systematic review of related literature on water-pipe use was conducted, and for this purpose, 76 articles were examined in the study. In this vein, geographic distribution and time trends of water-pipe consumption in Iran were considered. The results of this study showed that lifetime, last-year, and last-month prevalence of water-pipe smoking use among Iranian students were 28.78 (25.07–32.49), 20.84 (16.01–25.66), and 16.36 (11.86–20.85), respectively. The results also showed a wide variation by the region and sex in Iran. This study has shown the importance of addressing public prevention and alerting programs in schools and universities.